Microbial Production of Ethanol From Sludge Derived From an Urban Wastewater Treatment Plant - Godoy, Patricia; Mourenza, Álvaro; Hernández-Romero, Sergio; González-López, Jesús; Manzanera, Maximino (Frontiers in Microbiology, 2018)
A collection of lipase-producing microorganisms was isolated from sludge derived from an urban wastewater treatment plant. The microorganisms with the highest levels of lipase activity were selected in order to use triglycerides present in the sludge effectively and were then transformed with pdc:adhB genes for the production of ethanol. The transgenic strains showed high growth rates in diluted sludge and produced lipase protein in order to utilize fat present in the sludge, which provides an abundant source of carbon. Using sludge derived from treated wastewater as nutrient source, ethanol was produced by certain transgenic species belonging to the genera Proteus. Different forms of sludge were tested for maximal ethanol production, with dehydrated sludge being found to produce the best performance.